Happiness disparities in South Africa: an analysis of trends and determinants - Mathentamo, Qaqambile (My University, 2018)
The fast-growing prominence of happiness inequality is accompanied by a slow growth of happiness inequality literature. The happiness inequality literature is coming amidst growing concerns about the legitimacy of income inequality as a measure of inequality. The paper aims to be part of the growing happiness inequality literature by investigating these following equations: Is happiness inequality also increasing similarly to income inequality in South Africa, and how do determinants of happiness affect happiness inequality? South Africa is an unequal society it is therefore, imperative to ascertain whether inequality is high when inequality is measured in happiness inequality. Happiness inequality (decreasing) trends differently from income inequality (increasing). This means that happiness inequality may be a supplement measure of inequality together with income inequality since happiness inequality is decreasing. In addition, this paper’s trend findings are limited since the paper’s trend is based on only four years of survey. It is possible that a longer period of data might show a different trend. Some of the paper’s determinants results are similar to previous studies; especially the relationship between income inequality and happiness inequality. Previous studies found no relationship between income inequality and happiness inequality, the paper founds the same results.
A Research Report submitted in partial fulfilment of the Degree of Master of Commerce (Economic Science) ECON7008A Master’s Programme: 50% CC011in the School of Economic and Business Sciences, University of the Witwatersrand
Keywords: Income distribution; Economic development; Cost and standard of living